Employee Performance Management Information Systems: A Systematic Literature Review - Muhammad Dani Wahyudi (Journal of Technology and System Information, 2026)
The accelerated digital transformation of human resource management has intensified the need for integrated systems capable of monitoring and evaluating employee performance in a systematic and data-driven manner. This study aims to examine the development trajectories, implementation patterns, and effectiveness of Employee Performance Management Information Systems (EPMIS) across diverse organizational settings. Employing a Systematic Literature Review (SLR) approach, this research adheres to the PRISMA framework to ensure methodological rigor, transparency, and replicability. Data were collected from major academic databases, resulting in the selection of 30 empirical studies published between 2021 and 2026, which were subsequently analyzed using qualitative synthesis techniques. The findings demonstrate that the adoption of EPMIS contributes significantly to enhanced transparency, accountability, and administrative efficiency in both public and private sector organizations. Additionally, these systems facilitate objective and continuous performance evaluation through real-time data integration, thereby positively influencing employee motivation and work discipline. Nevertheless, the effectiveness of EPMIS implementation is contingent upon several moderating factors, including the availability of adequate technological infrastructure, the level of digital literacy among users, and the extent of organizational readiness for digital transformation. Challenges in these areas may hinder optimal system utilization and reduce overall impact. In conclusion, EPMIS represents a strategic instrument for improving employee performance management; however, its successful implementation requires comprehensive organizational support, continuous capacity building, and alignment between technological systems and human resource competencies.